Palladium-catalyzed regio- and stereoselective synthesis of aryl and 3-indolyl-substituted 4-methylene-3,4-dihydroisoquinolin-1(2H)-ones - Nori, Valeria; Arcadi, Antonio; Carlone, Armando; Marinelli, Fabio; Chiarini, Marco (Beilstein Journal of Organic Chemistry, 2020)
Cascade cyclocarbopalladation of the readily available aryl/alkyl-substituted propargylic amides containing an aryl iodide moiety, followed by Suzuki–Miyaura coupling with arylboronic acids, allowed an efficient regio- and stereoselective synthesis of tetrasubstituted 4-methylene-3,4-dihydroisoquinolin-1(2H)-ones. Moreover, cascade cyclocarbopalladation, followed by the reaction with 2-alkynyltrifluoroacetanilides, accomplished a double cyclization to afford challenging 4-methylene-3,4-dihydroisoquinolin-1(2H)-ones bearing a 3-indolyl substituent through aminopalladation/reductive elimination.
Keywords: alkynylanilines; arylboronic acids; indoles; isoquinolinones; palladium

(untitled) - Pettit, G. R.; Meng, Y.; Herald, D. L.; Graham, K. A. N.; Pettit, R. K.; Doubek, D. L. (J. Nat. Prod., 2003)

(untitled) - Glushkov, V. A.; Shklyaev, Y. V. (Chem. Heterocycl. Compd., 2001)

(untitled) - Jin, Z. (Nat. Prod. Rep., 2013)

(untitled) - Bhadra, K.; Suresh Kumar, G. (Mini-Rev. Med. Chem., 2010)

(untitled) - Giri, P.; Suresh Kumar, G. (Mini-Rev. Med. Chem., 2010)

(untitled) - Ruchelman, A. L.; Houghton, P. J.; Zhou, N.; Liu, A.; Liu, L. F.; LaVoie, E. J. (J. Med. Chem., 2005)

(untitled) - Saeed, A.; Ashraf, Z. (Pharm. Chem. J., 2008)

(untitled) - Guastavino, J. F.; Barolo, S. M.; Rossi, R. A. (Eur. J. Org. Chem., 2006)

(untitled) - Matsui, T.; Sugiura, T.; Nakai, H.; Iguchi, S.; Shigeoka, S.; Takada, H.; Odagaki, Y.; Nagao, Y.; Ushio, Y.; Ohmoto, K.; Iwamura, H.; Yamazaki, S.; et al. (J. Med. Chem., 1992)

WO Patent - Plettenburg, O.; Lorenz, K.; Goerlitzer, J.; Löhn, M. (Substituted isoquinolines and their use as rho-kinase inhibitors, 2008)

(untitled) - Li, S. W.; Nair, M. G.; Edwards, D. M.; Kisliuk, R. L.; Gaumont, Y.; Dev, I. K.; Duch, D. S.; Humphreys, J.; Smith, G. K.; Ferone, R. (J. Med. Chem., 1991)

(untitled) - Vinod, K. R.; Chandra, S.; Sharma, S. K. (Toxicol. Mech. Methods, 2010)

(untitled) - Hudlicky, T.; Rinner, U.; Gonzalez, D.; Akgun, H.; Schilling, S.; Siengalewicz, P.; Martinot, T. A.; Pettit, G. R. (J. Org. Chem., 2002)

(untitled) - Francis, S.; Croft, D.; Schüttelkopf, A. W.; Parry, C.; Pugliese, A.; Cameron, K.; Claydon, S.; Drysdale, M.; Gardner, C.; Gohlke, A.; Goodwin, G.; Gray, C. H.; et al. (Bioorg. Med. Chem. Lett., 2019)

(untitled) - Takwale, A. D.; Jeon, Y. U.; Lee, D. H.; Kim, H. J.; Hwang, J. Y. (Tetrahedron Lett., 2019)

(untitled) - Beng, T. K.; Langevin, S.; Farah, A. O.; Goodsell, J.; Wyatt, K. (New J. Chem., 2019)

(untitled) - Xie, H.; Xing, Q.; Shan, Z.; Xiao, F.; Deng, G.-J. (Adv. Synth. Catal., 2019)

(untitled) - Yang, Z.; Jie, L.; Yao, Z.; Yang, Z.; Cui, X. (Adv. Synth. Catal., 2019)

Handbook of Cyclization Reactions - Ma, S. (Wiley-VCH, 2010)

(untitled) - Sperger, T.; Le, C. M.; Lautens, M.; Schoenebeck, F. (Chem. Sci., 2017)

(untitled) - Blouin, S.; Gandon, V.; Blond, G.; Suffert, J. (Angew. Chem., Int. Ed., 2016)

(untitled) - Le, C. M.; Hou, X.; Sperger, T.; Schoenebeck, F.; Lautens, M. (Angew. Chem., Int. Ed., 2015)

(untitled) - Milde, B.; Leibeling, M.; Pawliczek, M.; Grunenberg, J.; Jones, P. G.; Werz, D. B. (Angew. Chem., Int. Ed., 2015)

(untitled) - Kan, S. B. J.; Anderson, E. A. (Org. Lett., 2008)

(untitled) - Bour, C.; Blond, G.; Salem, B.; Suffert, J. (Tetrahedron, 2006)

(untitled) - Düfert, A.; Werz, D. B. (Chem. – Eur. J., 2016)

(untitled) - Peshkov, A. A.; Peshkov, V. A.; Pereshivko, O. P.; Van Hecke, K.; Kumar, R.; Van der Eycken, E. V. (J. Org. Chem., 2015)

(untitled) - Nandakumar, A.; Perumal, P. T. (Org. Lett., 2013)

(untitled) - Charpenay, M.; Boudhar, A.; Siby, A.; Schigand, S.; Blond, G.; Suffert, J. (Adv. Synth. Catal., 2011)

(untitled) - Richey, R. N.; Yu, H. (Org. Process Res. Dev., 2009)

(untitled) - Mondal, A.; Kundu, P.; Jash, M.; Chowdhury, C. (Org. Biomol. Chem., 2018)

(untitled) - Arcadi, A.; Blesi, F.; Cacchi, S.; Fabrizi, G.; Goggiamani, A.; Marinelli, F. (J. Org. Chem., 2013)

(untitled) - Arcadi, A.; Cacchi, S.; Fabrizi, G.; Goggiamani, A.; Iazzetti, A.; Marinelli, F. (Org. Biomol. Chem., 2013)

(untitled) - He, Y.-P.; Wu, H.; Wang, Q.; Zhu, J. (Angew. Chem., Int. Ed., 2020)

(untitled) - Arcadi, A.; Cacchi, S.; Marinelli, F. (Tetrahedron Lett., 1992)

(untitled) - Cacchi, S.; Fabrizi, G.; Lamba, D.; Marinelli, F.; Parisi, L. M. (Synthesis, 2003)

(untitled) - Arcadi, A.; Cacchi, S.; Fabrizi, G.; Marinelli, F. (Synlett, 2000)

(untitled) - Arcadi, A.; Cacchi, S.; Fabrizi, G.; Marinelli, F.; Parisi, L. M. (J. Org. Chem., 2005)

(untitled) - Arcadi, A.; Cianci, R.; Ferrara, G.; Marinelli, F. (Tetrahedron, 2010)

(untitled) - Yao, B.; Wang, Q.; Zhu, J. (Angew. Chem., Int. Ed., 2013)

(untitled) - Arcadi, A.; Aschi, M.; Chiarini, M.; Ferrara, G.; Marinelli, F. (Adv. Synth. Catal., 2010)

(untitled) - Ostrowska, S.; Rogalski, S.; Lorkowski, J.; Walkowiak, J.; Pietraszuk, C. (Synlett, 2018)

(untitled) - Asgari, M. S.; Mirzazadeh, R.; Larijani, B.; Rashidi Ranjbar, P.; Rahimi, R.; Mahdavi, M. (Synlett, 2019)

(untitled) - Pierce, C. J.; Larsen, C. H. (Green Chem., 2012)

(untitled) - Ranjan, A.; Deore, A. S.; Yerande, S. G.; Dethe, D. H. (Eur. J. Org. Chem., 2017)

(untitled) - Arcadi, A.; Cacchi, S.; Carnicelli, V.; Marinelli, F. (Tetrahedron, 1994)

(untitled) - Montgomery, S. L.; Mangas-Sanchez, J.; Thompson, M. P.; Aleku, G. A.; Dominguez, B.; Turner, N. J. (Angew. Chem., Int. Ed., 2017)